Evaluation of tribological properties of laser textured hardened tool steels - Jana Šugárová; Martin Frnčík; Martin Necpal; Jana Moravčíková; Martin Kusý (Advances in Mechanical and Materials Engineering, 2016)
In this paper the laser surface texturing (LST) technology as one of the methods of tribological properties modifying of mating steel surfaces is analysed. The area density of dimple-like depression along with the dimple diameter are the only main factors which significantly influence the friction coefficient value, therefore the effect of different values of area density of dimples: 6 %, 11 % and 16 % on the contact coefficient of friction was analysed. Surface textures were manufactured on the planar areas of compression platens (90MnCrV8 tool steel) using a pulsed-beam laser. The values of coefficients of friction were obtained via a ring compression test. Test sample compression was realized in lubrication-free and hydrodynamic regime. A significant improvement of tribological properties in contact steel areas was experimentally observed in both friction regimes. The results of experiments showed that by applying of surface texturing with defined shape and dimensions of dimples and lubricating oil at the same time, the coefficient of friction value can be reduced to about of 75%.